On-Farm Composting of Agricultural Waste Materials for Sustainable Agriculture in Pakistan - Sarfraz Hashim; Muhammad Waqas; Ramesh P. Rudra; Alamgir Akhtar Khan; Asif Ali Mirani; Tariq Sultan; Farrukh Ehsan; Muhammad Abid; Muhammad Saifullah (Scientifica, 2022)
Agriculture is the economic backbone of Pakistan. 67% of country’s population resides in rural areas and primarily depends on agriculture. Pakistan's soils are poor in OM and have a low C : N ratio, and the overall fertility status is insufficient to support increased crop yields. Compost is an excellent alternative solution for improving soil OM content. However, this excellent alternative supply in Pakistan has yet to be used. Mass volumes of leaves, grass clippings, plant stalks, vines, weeds, twigs, and branches are burned daily. In this study, different compost piles (P1, P2, and P3) of compost were made using different agricultural and animal waste combinations to assess temperature, pH, and NPK. Results revealed that P3 demonstrated the most successful composting procedure. The temperature and pH levels throughout the composting process were determined in a specified range of 42–45oC and 6.1–8.3, respectively. Total nitrogen content ranged from 81.5 to 2175 ppm in farm compost. Total phosphorus concentrations range from 1.33 to 13.98 ppm, and potassium levels, on the other hand, range from 91.53 to 640 ppm in farm compost. The overall nitrogen concentration grew progressively between each pile at the end of a week. The varied concentrations revealed that adding various forms of agricultural waste would result in a variation in the quantity of NPK owing to microbial activity. On-farm composting has emerged as an effective technique for the sustainability of agricultural activities, capable of resolving crucial problems like crop residues and livestock waste disposal. Based on this study’s results, the pile (P3) combination shows the best NPK value performance and is recommended for agricultural uses to overcome the OM deficiency.